2024
DOI: 10.3390/app14051846
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of the Effect of Hydrogen Ratio on the Flame Stabilization and Blow-Off Dynamics of a Lean CH4/H2/Air Bluff-Body Flame

Lei Cheng,
Meng Zhang,
Shiyao Peng
et al.

Abstract: This study investigated the flame structure and dynamics of a bluff-body flame when numerically close to blow-off conditions. This includes the impact of the hydrogen ratio on lean CH4/H2/air flame stabilization and blow-off characteristics. In this study, we assessed the impacts of four different hydrogen ratios: 0%, 30%, 60%, and 90%. Large eddy simulation (LES) was coupled with a thickened flame (TF) model to determine the turbulent combustion using a 30-species skeletal mechanism. The numerical results wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…When the hydrogen composition increased, the flame became shorter and thicker, and its effect on the outer recirculation zone was minimized. A bluff-body-stabilized CH 4 /H 2 /air flame was investigated through large eddy simulation (LES) using hydrogen ratios of up to 90% [14]. The results showed that under stable conditions, both the flame height and the inner/outer recirculation zone decreased with an increase in the hydrogen ratio, and the flame tended to attach to the bluff body more strongly.…”
Section: Introductionmentioning
confidence: 99%
“…When the hydrogen composition increased, the flame became shorter and thicker, and its effect on the outer recirculation zone was minimized. A bluff-body-stabilized CH 4 /H 2 /air flame was investigated through large eddy simulation (LES) using hydrogen ratios of up to 90% [14]. The results showed that under stable conditions, both the flame height and the inner/outer recirculation zone decreased with an increase in the hydrogen ratio, and the flame tended to attach to the bluff body more strongly.…”
Section: Introductionmentioning
confidence: 99%